Impact of exchange rate volatility on international trade: Case of USA and Canada - Chrysanthi Balomenou; Erisa Pajollari (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2022)
Purpose: The aim of this study is to investigate the impact that exchange rate volatility has on international trade flows including here exports and imports. Design/methodology/approach: This study is based on quarterly data from 2000-2018 making 224 observations in total. To measure the relationship between the chosen variables, it was used VAR-Vector Autoregressive Model. One of the main advantages of this model is traced back at the fact that it allows for dynamic relationship specification. Given that we are dealing with financial and macroeconomic variables, the role of each variable cannot be expected to be immediately monitored. On the contrary, it could be expected that it takes time for the interrelationships to be obvious and manifested. All this justifies the use of VAR. In total, two equations each with three independent variables are used to answer to the research question. Regressors are selected after a deliberate literature review and they are: price level, GDP, exchange rate and its volatility. Findings: The results suggest that there exists indeed an impact of exchange rate volatility on international trade among the US and Canada. This relationship seems to be changing among months and at different levels of significance. The final findings indicate a positive long-run relationship between exchange rate volatility and exports. These results are in line with the findings that other researchers have concluded in their studies. Regarding the imports, there exists a long-run relationship, but its impact differs in different periods. Research limitations/implications: One of the limitations and also a recommendation for improvement, is the number of explanatory variables. This came as a result of some lack of data for the included period. Originality/value: This topic is not only of great importance to policy maker, but it is also an added value to the current literature on the matter as it provides a thorough up-to-date analysis. It also draws on a sample of considerable size, thus providing consistency.
Keywords: B17; F10; F19; P33; 330; Exchange Rate Volatility; Imports; Exports; USA; Canada